The spiritual influence of African traditional healers on moral behaviour and personhood: a focus on the Akamba of Mwala constituency in Kenya - Muasa, Sonia Kalondu (Nairobi : Maryknoll Institute of African Studies, 2018)
In partial fulfillment for the degree of masters of arts Maryknoll Institute of African studies of Saint Mary's university Nairobi and Winona, Minesota.
Keywords: Research -- Thesis. -- Kenya; Akamba (African people) -- social aspects -- spiritual aspects